High‐resolution Fourier‐encoded sub‐millisecond echo time musculoskeletal imaging at 3 Tesla and 7 Tesla. Issue 5 (11th December 2012) - Deligianni, X.; Bär, P.; Scheffler, K.; Trattnig, S.; Bieri, O.
<x xml:space="preserve">Abstract</x> Purpose The feasibility of imaging musculoskeletal fibrous tissue components, such as menisci, ligaments, and tendons, with a conventional spoiled gradient echo technique is explored in vivo at 3 T and 7 T. Methods To this end, the echo time (TE1) of a conventional Fourier‐encoded multicontrast three‐dimensional SGPR sequence is minimized by using nonselective excitation pulses, highly asymmetric readouts, and a variable TE1 along the phase and slice encoding direction. In addition, a fully sampled second echo image (with TE2 >> TE1) can be used to highlight components with short transverse relaxation times in a difference image with positive contrast. Results Fourier‐encoded spoiled gradient echo sequences are able to provide sub‐millisecond TE1 of about 800 μs for typical in‐plane resolutions of about 0.5 x 0.5 mm2. As a result, high‐resolution positive contrast images of fibrous tissues can be generated within clinically feasible scan‐time of about 2–7 minutes. Conclusion After optimization, Fourier‐encoded spoiled gradient echo provides a highly robust and flexible imaging technique for high‐resolution positive contrast imaging of fibrous tissue that can readily be used in the clinical routine. Magn Reson Med 70:1434–1439, 2013. © 2012 Wiley Periodicals, Inc.